A fretting fatigue model based on self-steered cracks. (February 2022) - Erena, Diego; Vázquez, Jesús; Navarro, Carlos; Domínguez, Jaime
Highlights: Fretting fatigue model based on a critical plane parameter. Simultaneous prediction of fretting fatigue cracks and total life. Fatigue life prediction considering crack initiation and propagation phases. Abstract: In this article a new fretting fatigue life prediction model is presented. The model can be classified as a variable crack initiation length: the crack initiation and crack propagation phases are calculated as a function of the crack initiation length, and among all the feasible crack initiation lengths and orientations, that producing the minimum fatigue life is considered. In this new proposal the crack direction is automatically determined as a function of fatigue parameters in both phases: initiation and propagation. The model is applied to a wide experimental campaign of fretting fatigue tests, and excellent correlation is obtained between experimental and predicted fretting fatigue lives and crack paths.